Enhancing the melting of phase change material using a fins–nanoparticle combination in a triplex tube heat exchanger. (March 2021) - Abdulateef, Ammar M.; Jaszczur, Marek; Hassan, Qusay; Anish, R; Niyas, Hakeem; Sopian, Kamaruzzaman; Abdulateef, Jasim
Highlights: A combination of fins–nanoparticle is studied numerically and experimentally. TTHX with longitudinal fins and TTHX with triangular fins are separately analyzed. Mass flow rates (16.2, 29.4 and 37.5 kg/min) for non steady state are investigated. An important enhancement for charging (milting) the PCM was with nanoparticle. Abstract: A combination of heat transfer augmentation techniques is highly necessary to enhance the performance of Thermal Energy Storage (TES) systems employed in a wide range of applications. The major issue is that many of the Phase Change Materials (PCMs) possess low thermal conductivity ( k ≤ 0.2 W/m K), resulting in an inefficient melting process. Triplex Tube Heat Exchanger (TTHX) based TES system is both numerically and experimentally studied using Paraffin (RT82) with Alumina (Al2 O3 ) nanoparticles that has a charging temperature in the range of 78.15–82.15 ∘ C . The experimental findings indicate that the Paraffin is not completely melted within the required time of four hours for the inside heating method at 97 ∘ C . The Paraffin is successfully melted for both sides heating at 90 ∘ C in lesser time and average temperature than the outside heating. With different charging temperatures, the Paraffin melting was consumed a short time for the non steady state at the mass flow rate of 29.4 kg/min, compared with the 16.2 and 37.5 kg/min for inner and outer tubes. Other outcomes were that with the fins–nanoparticle combination, an improved performance for melting the Paraffin, compared with those that occurred without nanoparticle. Furthermore, in the numerical study, compared with the pure Paraffin case, the melting time was minimized for TTHX with longitudinal fins (12%) and TTHX with triangular fins (22%) for the PCM having 10% nanoparticle, respectively. Close agreement is found between the numerical and experimental findings.